Do You Remember Mitochondria? - Messina, Flavia; Cecconi, Francesco; Rodolfo, Carlo (Frontiers in Physiology, 2020)
Dementia is one among the consequences of aging, and amnesia is often one of the most common symptoms. Lack of memory, due to both “healthy” aging and neurodegenerative conditions, such as in Alzheimer’s disease, has a dramatic impact on the patient’s lifestyle. In fact, the inability to recall information made by a previous experience could not only alter the interaction with the environment, but also lead to a loss of identity. Mitochondria are key regulators of brain’s activity, thanks to their “dynamic organelles” nature they constantly rearrange in the cell body and move along axons and dendrites, changing in dimension, shape, and location, accordingly to the cell’s energy requirements. Indeed, the energy they can provide is essential to maintain synaptic plasticity and to ensure transmission through presynaptic terminals and postsynaptic spines. Stressful conditions, like the ones found in neurodegenerative diseases, seriously impair mitochondria bioenergetic, leading to both loss of proper neuronal interaction and of neuron themselves. Here we discuss the current knowledge about the role of mitochondria and mitochondrial dynamics in relation to neurodegenerative disorders linked to aging. Furthermore, we highlighted the obstacles as well as the future perspectives aimed to enlarge our knowledge about mitochondria as target for new therapeutic strategies to slow down ageing and neurodegenerative disease’s symptoms.